Exploratory and Confirmatory Factor Analysis of a Workforce Equity Scale for Government Employees - Balila, Jolly; Balila, Edwin (12th International Scholars Conference 2025, 2026)
This study evaluated the psychometric structure of a workforce equity instrument administered to 526 permanent civil service–eligible government employees. The Kaiser–Meyer–Olkin measure and Bartlett’s test of sphericity were used to verify the suitability of the data. Exploratory factor analysis (EFA) results revealed a three‑factor solution as the best fit. Each factor emerged with high internal consistency (Cronbach’s α > 0.90), suggesting robust reliability. The three factors were labeled as Fair Work Distribution and Evaluation, Equitable Hiring Practices, and Equal Access to Career Growth—each consisting of four items, drawn from an original pool of 25 items. Subsequently, confirmatory factor analysis tested this three‑factor model. Fit indices indicated strong model adequacy: Comparative Fit Index (CFI = 0.963) and Tucker‑Lewis Index (TLI = 0.952), both exceeding the conventional 0.95 threshold; Root Mean Square Error of Approximation (RMSEA = 0.093), slightly above the ideal < 0.08 range but acceptable given the high CFI/TLI; and a significant chi‑square statistic (χ² = 280.56, df = 51, p < 0.001. The overall results support a three‑factor measurement model that generated a distinct dimension of workforce equity. These findings affirm the construct validity of the workforce scale and justify its division into three subscales aligned with specific latent constructs. Future applications may employ this instrument for assessing equity perceptions in public sector employment contexts and for informing targeted organizational policy interventions.